1999
DOI: 10.1046/j.1469-8137.1999.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various organic compounds on growth and phosphorus uptake of an arbuscular mycorrhizal fungus

Abstract: The influence of three organic compounds and bakers' dry yeast on growth of external mycelium and phosphorus uptake of the arbuscular mycorrhizal fungus Glomus intraradices Schenck & Smith (BEG 87) was examined. Two experiments were carried out in compartmentalized growth systems with root-free sand or soil compartments. The sand and soil in the root-free compartments were left untreated or uniformly mixed with one of the following substrates (0n5 mg g −" soil) : bakers' dry yeast, bovine serum albumin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 22 publications
(26 reference statements)
5
61
1
Order By: Relevance
“…The neutral lipid-tophospholipid ratio in AM fungi thus indicates the relative allocation to storage. An effect similar to the effect that we observed (i.e., lower relative allocation to storage with a high nutrient level) has been observed previously in response to P and to other nutrient sources (12,29). Thus, the AM fungus has a strategy to increase the C allocated to reserves and resistant propagules in mycelia in environments with low nutrient levels.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The neutral lipid-tophospholipid ratio in AM fungi thus indicates the relative allocation to storage. An effect similar to the effect that we observed (i.e., lower relative allocation to storage with a high nutrient level) has been observed previously in response to P and to other nutrient sources (12,29). Thus, the AM fungus has a strategy to increase the C allocated to reserves and resistant propagules in mycelia in environments with low nutrient levels.…”
Section: Discussionsupporting
confidence: 70%
“…AM fungi may have higher C gain at locations in which roots are in direct contact with enriched medium. Thus, AM fungal proliferation could occur as a response to P-enriched patches (12) in a manner similar to the manner observed for organic nutrients (29,34). Later, when P levels in plants become saturated, the overall C allocation to the AM fungus decreases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, St John et al (1983) and Friberg (2001) found that AM fungal hyphae grew best in soils with a high amount of organic matter which is shown in our results also. Ravnskov et al (1999) had shown that effects of organic compounds on growth of AM fungi in soil vary according to chemical composition of the substrate which was similar to present study. The present result has shown that Lantana and Eupatorium are better than other treatments.…”
Section: Discussionsupporting
confidence: 80%
“…AM fungi could also be involved in the acquisition of organic N. Preliminary studies have demonstrated that the development of the extraradical mycelium of AM fungi is stimulated by external organic N sources (St. John et al, 1983a, 1983bJoner and Jakobsen, 1995;Ravnskov et al, 1999). Näsholm et al (1998) obtained indirect evidence of amino acid uptake from Deschampsia flexuosa colonized by AM fungi in field conditions.…”
mentioning
confidence: 95%